Improving AUD Language Skills Through the ABC 5 Dasar Game at TK IT Permatasari Kids School Boyolali - mardinta, anisa putri; Ambari Sumanto, Reni Pawestuti (Jurusan PGPAUD FIP UNNES, 2023)
The low language skills of early childhood during the current pandemic need to be developed. In this case, the principle of learning from home through ABC 5 Dasar games is considered very suitable for the characteristics of childrens because the principle of learning in kindergarten is learning while playing. This study aims to determine whether there is an increase in language skills through ABC 5 Dasar games for 5-6 years old at TK IT Permatasari Kids School Boyolali. The research method used in this research is quantitative by using the One Group pretest – posttest. The sample used is the class B which collects 33 respondents. This research was conducted from August to September 2021. The results showed that the ABC 5 Dasar games could improve language skills in the class B at TK IT Permatasari Kids School Boyolali. This can be seen from the results of descriptive analysis with the number of respondents of 33 childrens with a value of t = -43,773 with a significance level of = 0.000, the language skills of early childhood after the application of the basic 5 basic ABC games are higher. The Percentage Value of early childhood language skills based on the application of the ABC 5 Dasar games has increased by 26.16%. Therefore it can be said that early childhood language skills increased after being given the ABC 5 Dasar games. The suggestions proposed in this study include: (1) to be able to use more interesting game media as a medium for learning language skills in early childhood. (2) Parents should be able to provide sufficient stimulation to children.